Student writing in the engineering curriculum: discursive rhetorical model of the laboratory report genre in Spanish - Sologuren, Enrique (Frontiers in Psychology, 2023)
The laboratory report is a widely used genre in the academic training process in civil computer engineering. Students produce this genre in the university classroom for diverse academic and professional purposes. Despite its relevance, empirical rhetorical-discursive descriptions of the value of student writing are still scarce in Spanish. Thus, we describe the rhetorical-discursive organization of the laboratory report genre in this subdiscipline. To fulfil this purpose, we followed a methodological design based on Swalesian Genre Analysis and used a corpus of ninety-eight texts. The sample was collected in a self-compiled form through consultation with teachers and students in the university classroom. The application of this method allowed us to determine the macro-moves, moves, and rhetorical steps of the genre, its communicative functions, and textual features. The resulting rhetorical model consisted of four macro-moves, twelve moves and seventeen steps. This model shows the highly dynamic and mesogeneric nature of this genre, the new functions of multimodal artefacts, and the genre's presence across the curriculum. To know about the teachers' and students' views on the process of training professional writers in engineering, the rhetorical model was complemented with an ethnographic phase (in the terms proposed by Swales: corroboration process with a couple of members of the community) before and after collecting the textual corpus. Finally, implications for genre theory, Spanish language description, and genre pedagogy emerge from the results.